STRATEGI PENGEMBANGAN DAYA TARIK WISATA KOTA TUA AMPENAN KOTA MATARAM - Rizal Kurniansah; Triony Septia Susana SP; Srilian Laxmiwaty Dai (Tulisan Ilmiah Pariwisata (TULIP), 2021)
The purpose of this study is to describe the strategy of developing a tourist attraction in the old town of Ampenan, Mataram. This type of research is qualitative research, data collection methods are observation, interviews, literature study, and documentation. The data analysis used in this research is SWOT analysis. Based on the results of the research conducted, the following strategies are produced: SO (Strength Opportunities) strategy, namely community empowerment through training, utilizing technological advances in marketing Ampenan Old Town, increasing collaboration with travel agencies and making more tour packages to Ampenan Old Town. The WO (Weakness Opportunities) strategy is: developing and managing supporting facilities in the tourist attraction of the old city of Ampenan, conducting promotions in collaboration with stakeholders, making attractive tour packages. The ST (Strength Threath) strategy is: making special rules/policies in the development of ampenan old town, working with related agencies in tackling environmental damage,. The WT (Weakness Threath) strategy is: conducting outreach to the local community, increasing supervision of tourism activities, maximizing the tourism development budget through cooperation